A Novel Approach for Mining Polymorphic Microsatellite Markers In Silico - Hoffman, Joseph I. (Public Library of Science, 2011)

(untitled)
An important emerging application of high-throughput 454 sequencing is the isolation of molecular markers such as microsatellites from genomic DNA. However, few studies have developed microsatellites from cDNA despite the added potential for targeting candidate genes. Moreover, to develop microsatellites usually requires the evaluation of numerous primer pairs for polymorphism in the focal species. This can be time-consuming and wasteful, particularly for taxa with low genetic diversity where the majority of primers often yield monomorphic polymerase chain reaction (PCR) products. Transcriptome assemblies provide a convenient solution, functional annotation of transcripts allowing markers to be targeted towards candidate genes, while high sequence coverage in principle permits the assessment of variability in silico. Consequently, we evaluated fifty primer pairs designed to amplify microsatellites, primarily residing within transcripts related to immunity and growth, identified from an Antarctic fur seal (Arctocephalus gazella) transcriptome assembly. In silico visualization was used to classify each microsatellite as being either polymorphic or monomorphic and to quantify the number of distinct length variants, each taken to represent a different allele. The majority of loci (n = 36, 76.0%) yielded interpretable PCR products, 23 of which were polymorphic in a sample of 24 fur seal individuals. Loci that appeared variable in silico were significantly more likely to yield polymorphic PCR products, even after controlling for microsatellite length measured in silico. We also found a significant positive relationship between inferred and observed allele number. This study not only demonstrates the feasibility of generating modest panels of microsatellites targeted towards specific classes of gene, but also suggests that in silico microsatellite variability may provide a useful proxy for PCR product polymorphism.